One-Pot Conversion of Furfural to γ-Valerolactone over Co- and Pt-Doped ZSM-5 Catalysts - Tolek, Weerachon; Auppahad, Warucha; Weerachawanasak, Patcharaporn; Mekasuwandumrong, Okorn; Praserthdam, Piyasan; Panpranot, Joongjai (My University, 2023)
γ-Valerolactone (GVL) is one of the useful biomass compounds produced via different reaction pathways from hemicellulose. In this study, Co- and Pt-doped/ZSM-5 catalysts with different Co loadings (0–10 wt.%) and Pt loadings (0.5–2 wt.%) were prepared by impregnation method and employed in a one-pot conversion of furfural to GVL. The yield of GVL increased with increasing reaction temperature from 100 to 140 °C. At the reaction temperature of 120 °C, higher amounts of secondary products such as AL and IPL can be converted to GVL, especially on the Co- and Pt-modified ZSM-5 catalysts. Compared to the non-modified H-ZSM-5 (GVL yield 35.4%), Co- and Pt-doped ZSM-5 catalysts exhibited much higher yield of GVL with the 1%Pt/ZSM-5 catalyst showing the highest yield of GVL at 85.4% at 120 °C and 1 bar N2 without the use of liquid acid or external H2 supply. The catalyst performances were correlated to the physicochemical properties of the catalysts such as the amount and type of acid sites. The NH3-TPD and in situ FTIR spectra of pyridine adsorption results revealed that Co- and Pt-loaded on ZSM-5 enhanced Lewis and weak acid sites, which are beneficial for the reaction. The results present a simple strategy to obtain high GVL yield under relatively mild conditions.
Keywords: furfural; furfuryl alcohol; one-pot conversion; ZSM-5; γ-valerolactone